(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
SmartMessages (SMs) are migratory execution units used to describe distributedcomputations over mobile adhoc networks of embedded systems. The main benefitsprovided by SMs are flexibility, scalability, and the ability to performdistributed computations over networks composed of heterogeneous, resourceconstrained, unattended embedded systems. A key challenge that confronts SMs,however, is how to define a security architecture that protects both the SMsand the hosts, while preserving the SM benefits. Inthis paper, we present a basic SM security architecture which sets up aframework for the security related issues of SMs and provides solutions forauthentication, authorization, and secure SM migration. Since this paper is thefirst attempt to investigate the unique security challenges posed by a systembased on mobile code executed over mobile ad hoc networks, we also discuss themain issues that remain to be solved for a more comprehensive SM securityarchitecture.